#### Answer

m+n=0 and mn=9

#### Work Step by Step

$(x+m)(x+n)=x^2+mx+nx+mn=x^2+(m+n)x+mn$
$=x^2+9$
Hence m+n=0 and mn=9

Published by
Cengage Learning

ISBN 10:
9781337271172

ISBN 13:
978-1-33727-117-2

m+n=0 and mn=9

$(x+m)(x+n)=x^2+mx+nx+mn=x^2+(m+n)x+mn$
$=x^2+9$
Hence m+n=0 and mn=9

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.